Opportunity and challenges for nanotechnology application for genome editing in plants - Sanskriti Vats; Surbhi Kumawat; Jashandeep Brar; Sukhmandeep Kaur; Karmveer Yadav; Sayali G. Magar; Pravin V. Jadhav; Prafull Salvi; Humira Sonah; Sandhya Sharma; Rupesh Deshmukh (Plant Nano Biology, 2022)
abstract: CRISPR-Cas9 genome editing systems have enormous promise in the areas of biomedical research and agriculture. While the effectiveness and utility of CRISPR have already been well established, there are many challenges in the successful application of CRISPR to plant systems. In this regard, nanotechnology could play a critical role in addressing some of the decisive challenges preventing CRISPR-mediated genome engineering in plants especially in recalcitrant species. Nanoparticles can be used as an efficient delivery agent to the targeted cell and enhance genome editing efficiency. The Nanoparticles-based delivery system can deliver functional gene, RNP, or siRNA intact into the plant cell resulting in the generation of genome-edited plants without transgenes. In this review, we have discussed various nanoparticle technologies that can overcome barriers associated with the CRISPR-mediated genetic transformation in plants, holding it to reach its full potential. CRISPR can be used to develop tolerance against various biotic and abiotic stresses. As well as, it may also be employed in improving food quality and productivity thereby providing food security to the ever-growing human population.